Tutankhamun and Carter assessing the impact of a major archaeological find - Sousa, Rogério 1969-; Pieke, Gabriele; Bagh, Tine 1961- (Oxbow Books, 2024)
"The discovery of the tomb of Tutankhamun in 1922 stands out as one of the most important finds of modern archaeology, revealing an enormous wealth of objects encapsulating techniques, vestiges of uses and re-uses of materials, as well as unrivalled clues regarding the complex set of beliefs associated with the pharaonic funerary material culture. Once cleared from the tomb, these objects have captivated the world with their irresistible charm and beauty ending up playing a role in contemporary popular culture. However, it seems that such magnetism rather hindered than facilitate the scholarly study of the find. One hundred years after the discovery of this magnificent tomb, most of its objects remain insufficiently studied to this day. This volume aims at showing how it remains challenging to study Tutankhamun's objects, gathering a collection of studies authored by leading scholars on conservation, materials, funerary believes, as well as the reception of motifs and the impact of the discovery. Through these studies it becomes clear how ancient objects can help us reconstruct the complex fabric of the ancient Egyptian society and how they keep interacting with modern audiences"
Keywords: Carter, Howard -- 1874-1939; Funde; Grab des Tutanchamun -- Tal der Könige; Tutankhamen / King of Egypt / Tomb; Carter, Howard / 1874-1939; Excavations (Archaeology) / Egypt; Egypt / Antiquities; Konferenzschrift -- 2023 -- Lissabon